2013
DOI: 10.1186/1475-2875-12-204
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent susceptibility of Anopheles gambiae M and S molecular forms and Anopheles arabiensis to Plasmodium falciparum infection in Burkina Faso

Abstract: BackgroundThe Anopheles gambiae sensu lato (s.l.) species complex in Burkina Faso consists of Anopheles arabiensis, and molecular forms M and S of Anopheles gambiae sensu stricto (s.s.). Previous studies comparing the M and S forms for level of infection with Plasmodium falciparum have yielded conflicting results.MethodsMosquito larvae were sampled from natural pools, reared to adulthood under controlled conditions, and challenged with natural P. falciparum by experimental feeding with blood from gametocyte ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
6
24
1
Order By: Relevance
“…This suggests a geographic scale of adaptation and sympatric association between the parasite and the vector. Similar reports of geographic scale of adaptation (Haris et al, 2012) and sympatric association (Gnémé et al, 2013) have been posited. This is also in agreement with the reports of Collins et al (1986), Molina-Cruz et al, (2012) that showed the survival of P. falciparum in A. gambiae mosquitoes seemed to correlate with their geographical origin.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This suggests a geographic scale of adaptation and sympatric association between the parasite and the vector. Similar reports of geographic scale of adaptation (Haris et al, 2012) and sympatric association (Gnémé et al, 2013) have been posited. This is also in agreement with the reports of Collins et al (1986), Molina-Cruz et al, (2012) that showed the survival of P. falciparum in A. gambiae mosquitoes seemed to correlate with their geographical origin.…”
Section: Discussionsupporting
confidence: 62%
“…For the infection experiment, the female mosquitoes were starved for 18 to 20 hours prior to feeding them with the infectious blood meal (Gnémé et al, 2013). On the 5 th day of emergence, the identified A. gambiae females were infected by allowing them to feed on an individual who had been diagnosed positive for infection by P. Falciparum, following the regulations of Department of Health and Human Services (HHS, 2009).…”
Section: Infection Of the F 1 A Gambiae Females With Plasmodium Falcmentioning
confidence: 99%
“…In order to collect a random sample of essentially unrelated individuals, fewer than ten larvae were collected from any one larval site and a single collection comprised larvae from >50 larval sites. Collections were done in the Sudan Savanna region of Burkina Faso in the village of Goundry (12°30′N, 1°20′W), 30 km N of the capital city, Ouagadougou, across months of the malaria transmission season of 2007 and 2008 [ 29 ]. Larvae were raised in Centre National de Recherche et de Formation sur le Paludisme (CNRFP) insectaries in Ouagadougou to adulthood under standard insectary conditions [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Collections were done in the Sudan Savanna region of Burkina Faso in the village of Goundry (12°30′N, 1°20′W), 30 km N of the capital city, Ouagadougou, across months of the malaria transmission season of 2007 and 2008 [ 29 ]. Larvae were raised in Centre National de Recherche et de Formation sur le Paludisme (CNRFP) insectaries in Ouagadougou to adulthood under standard insectary conditions [ 29 ]. Following emergence, 3-day old adults were challenged with wild P. falciparum by experimental infection.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the 1940s, A. gambiae was considered a single biologically variable species, but crossing studies and genetic analysis led to the naming of nine morphologically similar species that vary in their geographic distribution, geographic overlap with other complex members, and ecology (reviewed in Coetzee et al 2013). It is becoming increasingly appreciated from ecological distinctions and recent discoveries of additional genetic substructure that, even within species, Anopheles species frequently form partially reproductively isolated and differentiated subpopulations (Costantini et al 2009; Gnémé et al 2013; Lee et al 2013). As an example of this dynamic, a new subgroup of A. gambiae s.l.…”
Section: Introductionmentioning
confidence: 99%